2018
DOI: 10.1038/nature25743
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and mechanogating mechanism of the Piezo1 channel

Abstract: The mechanosensitive Piezo channels function as key eukaryotic mechanotransducers. However, their structures and mechanogating mechanisms remain unknown. Here we determine the three-bladed, propeller-like electron cryo-microscopy structure of mouse Piezo1 and functionally reveal its mechanotransduction components. Despite the lack of sequence repetition, we identify nine repetitive units consisting of four transmembrane helices each-which we term transmembrane helical units (THUs)-which assemble into a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
536
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(551 citation statements)
references
References 47 publications
14
536
0
1
Order By: Relevance
“…MSCs are mechanosensitive, and mechanical forces can induce ATP release, but the mechanisms for mechanical induction of ATP release from MSCs remain poorly understood . The Ca 2+ ‐permeable Piezo1 channel is a newly discovered mechanosensing mechanism in many types of cells . Furthermore, recent studies have reported that mechanical or chemical activation of the Piezo1 channel induces ATP release from endothelial cells, urothelial cells, and red blood cells .…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are mechanosensitive, and mechanical forces can induce ATP release, but the mechanisms for mechanical induction of ATP release from MSCs remain poorly understood . The Ca 2+ ‐permeable Piezo1 channel is a newly discovered mechanosensing mechanism in many types of cells . Furthermore, recent studies have reported that mechanical or chemical activation of the Piezo1 channel induces ATP release from endothelial cells, urothelial cells, and red blood cells .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the high‐resolution cryo‐EM structure of mouse Piezo1 has been determined . However, the dynamic process of mechanical control and regulation of the Piezo channel remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A channel with only one or two symmetrical blades is expected to respond to tension changes primarily along one axis, while three blades is the minimum for omnidirectional sensitivity. The three blades suggest rotation: does rotation of the blades produce a counter-rotation of the center that opens the pore, as suggested in Zhao et al [7]? The long blades hint at a large mechanical amplification so that a small change in membrane tension might be felt over a large membrane area.…”
mentioning
confidence: 97%
“…Earlier structural and functional studies have elucidated two gating mechanisms: mechanical forces acting either via the cytoskeleton [2,3] or through tension in the membrane [4]. Structural studies using cryoEM of mouse Piezo1 (mPiezo1) [57], a member of a newly discovered family of channels [8], lead to the suggestion of a third gating mechanism: channel opening in response to change in the local curvature of the membrane [5]. …”
mentioning
confidence: 99%
See 1 more Smart Citation